Spiraea sp. new natural host of Plum pox virus (Sharka) - Piglionico, Damián Gustavo (2021)
Plum pox virus (PPV) was detected in Argentina for the first time in 2004. After eradication of the initial outbreaks, establishment of quarantine areas and strict control of nursery stock plants, no evidence of disease spread was recorded. During spring 2018, symptoms, consisting of chlorotic rings, were observed on leaves of an ornamental plant of the Rosaceae family “Bridal Crown” (Spiraea sp.) in the garden of a house within the PPV quarantine area in San Rafael, Mendoza province. Symptomatic leaves were analyzed for PPV by DAS-ELISA with positive results. The presence of the virus was confirmed by conventional and qRT-PCR and the use of “GF-305” biological indicator plants inoculated by T-bud grafting with buds from the Spiraea. A 243 bp PCR fragment amplified from the Spiraea samples, and corresponding to the carboxy-terminal region of PPV coat protein gene was isolated, sequenced, and deposited in GenBank (MN587037). It showed 99% identity to other PPV isolates. RT-qPCR, confirmed the virus as being an isolate of the PPV D strain previously found in the quarantine areas. Our results confirm PPV natural infection on a new ornamental host, “Bridal Crown”, which does not belong to the genus Prunus, warning of the potential danger of the species as a host of, and a source of, inoculum for PPV.